2016
DOI: 10.1016/j.chom.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Fap2 Mediates Fusobacterium nucleatum Colorectal Adenocarcinoma Enrichment by Binding to Tumor-Expressed Gal-GalNAc

Abstract: SUMMARY Fusobacterium nucleatum is associated with colorectal cancer and promotes colonic tumor formation in preclinical models. However, fusobacteria are core members of the human oral microbiome and less prevalent in the healthy gut, raising questions about how fusobacteria localize to CRC. We identify a host polysaccharide and fusobacterial lectin that explicates fusobacteria abundance in CRC. Gal-Gal-NAc, which is overexpressed in CRC, is recognized by fusobacterial Fap2, which functions as a Gal-Gal-NAc l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
549
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 562 publications
(590 citation statements)
references
References 47 publications
(62 reference statements)
11
549
3
2
Order By: Relevance
“…F. nucleatum attaches to the host epithelial E-cadherin and promotes colorectal carcinogenesis via the fusobacterial adhesin FadA(Rubinstein et al, 2013). The interaction between a host polysaccharide, Gal-GalNAc with fusobacterial lectin (Fap2) facilitates F. nucleatum enrichment in CRC tissues (Abed et al, 2016). However, it is unknown whether and how F. nucleatum may mediate chemoresistance in CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…F. nucleatum attaches to the host epithelial E-cadherin and promotes colorectal carcinogenesis via the fusobacterial adhesin FadA(Rubinstein et al, 2013). The interaction between a host polysaccharide, Gal-GalNAc with fusobacterial lectin (Fap2) facilitates F. nucleatum enrichment in CRC tissues (Abed et al, 2016). However, it is unknown whether and how F. nucleatum may mediate chemoresistance in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…F. nucleatum adhesin FadA may bind to the E-cadherin protein and promote colorectal carcinogenesis (Rubinstein et al, 2013). In addition, F. nucleatum lectin Fap2 may recognize the host Gal-GalNAc and help this bacterium localize abundantly in colon cancer epithelial cells (Abed et al, 2016). However, the potential effect of F. nucleatum on chemotherapy is not examined in human literature.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, hydrogen sulfide produced by F. nucleatum or other microbial species may be promoting tumorigenesis by damaging host cells and DNA. Indeed, F. nucelatum has well established mechanistic links to CRC tumor development [37,6365], albeit, unrelated to hydrogen sulfide production. On the other hand, metabolomics profiles identify no source agent (host, microbe, microbial species).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, quantifying the relative abundance of hydrogen sulfide-producing bacteria is far less challenging. Sulfidogenic bacteria such as Bilophila wadsworthia , Fusobacterium species, and sulfur-reducers such as Desulfovibrio species have all been identified within the gut and linked to colon inflammation [32], adenomas [21,33,34], and colon tumors [3537]. However, these microbial associations are not sufficient for determining microbial metabolite production.…”
Section: Introductionmentioning
confidence: 99%
“…When its ligands (for instance, Fap2) bind to TIGIT, NK cells stop killing their target cancer cells. Coppenhagen-Glazer et al demonstrated that Fap2 co-aggregates other microorganisms and attaches to the mammalian cell surface by binding to galactose- and N-acetyl-d-galactosamine (Gal / GalNAc) (78). Abed et al showed evidence that enrichment of Fn in CRC tumor tissues, as opposed to normal tissues surrounding these tissues, may be due to selective binding of Fap2 to Gal/GalNAc, which is over expressed on the surface of tumor cells (78).…”
Section: Possible Explanation Of Why Fusobacterium Infection Is Assocmentioning
confidence: 99%